Pengaruh Supervisi Akademik Dan Profesionalisme Guru Terhadap Kinerja Guru Sma Se-Kecamatan Lengkiti - Rusdiana Rusdiana; Edi Harapan; Nuril Furkan (Departement of Mathematics Education, 2023)
This study aims to identify and describe: 1). the effect of academic supervision on teacher performance;2) the effect of teacher professionalism on teacher performance, 3) the effect of academic supervision and teacher professionalism on the performance of high school teachers in Lengkiti District. This study uses a quantitative descriptive method. The population and sample in this study were 63 high school teachers in Lengkiti District, with the sample technique used was total sampling. The data collection technique used is a questionnaire. Data were analyzed using simple linear and multiple linear regression formulas using the SPSS (Statistical Product and Services Solution) program. The results of the study show that: 1) There is a significant effect of academic supervision on the performance of high school teachers in Lengkiti District; 2) There is a significant influence of teacher professionalism on the performance of high school teachers in Lengkiti District; 3) There is a significant influence of academic supervision and teacher professionalism on the performance of high school teachers in Lengkiti District. This can be seen from the results of the F-test which shows a significance value of 0.000 <0.005. The influence of academic supervision and teacher professionalism together on teacher performance is 78.6%, the remaining 21.4% is influenced by other factors.